Politics, Policy and the Discourses of Heritage in Britain - Waterton, E. author. aut Link
XI, 260 p.
Keywords: This book offers a critique of the dominant conceptualization of heritage found in policy, which tends to privilege the white, middle and upper classes. Using Britain as an illustration, Waterton explores how and why recent policies continue to lean towards the predictable melding of cultural diversity with tendencies of assimilation.